José Rebello da Silva: pioneer of the Brazilian guitar and the marches of Ameno Resedá (Orfeu, 2023)
José Rebello da Silva (1884-1951), also known as José (or Zé) Cavaquinho, played a multifaceted role in Rio de Janeiro’s music scene in the first half of the 20th century, as a guitarist, cavaquinho player, flutist, composer, teacher, and conductor, in addition to having been one of the founding members and musical director of the Carnaval group Ameno Resedá. Despite the recognition by the press and his peers during his lifetime, his name ended up being relegated to oblivion, as well as those of countless others, creating substantial gaps in the historiography of Brazilian music. Based on bibliographical sources, scores and information from newspapers and magazines of the time, this article aims to shed more light on José Rebello’ story, seeking to preserve his memory and bring his name back in circulation.
Keywords: José Rebello da Silva; José Cavaquinho; Ameno Resedá; Yvonne Rebello; brazilian guitar